Conductive paste, rfid inlay, method for producing rfid inlay, use of conductive paste for bonding chips and use of conductive paste for obtaining rfid inlay

By using a specific combination of conductive paste, a conductive paste containing high molecular weight aromatic urethane acrylate and low molecular weight polymerizable monomer, combined with conductive particles, the conductivity reliability and connection stability in high temperature and high humidity environment are solved. The high-precision RFID inlay manufacturing is achieved.

CN119137686APending Publication Date: 2024-12-13SEKISUI CHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037434.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-08
Filing Date
2023-07-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing conductive paste is difficult to fine wiring in high-precision configuration, resulting in low conduction reliability and reduced connection reliability in high temperature and high humidity environments.

Method used

A conductive paste containing an aromatic urethane acrylate having a molecular weight of 1000 or more and a polymerizable monomer having a molecular weight of less than 1000 is used, and the viscosity is 5 Pa·s to 50 Pa·s at 25°C, and 3 to 30 parts by weight of conductivity. The adhesive part is formed by heating and pressurization, and electrical connection is achieved by using conductive particles.

Benefits of technology

It improves the adhesion and conduction reliability of the conductive paste, and can maintain high connection stability under high temperature and high humidity environments, and is suitable for the manufacturing of RFID inlays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005109447840000291
    Figure BDA0005109447840000291
  • Figure BDA0005109447840000301
    Figure BDA0005109447840000301
  • Figure BDA0005109447840000311
    Figure BDA0005109447840000311
Patent Text Reader

Abstract

Provided is a conductive paste which has improved adhesiveness and improved conduction reliability. This conductive paste contains: a curable compound containing a urethane (meth) acrylate having an aromatic skeleton and a molecular weight of at least 1000; and a polymerizable monomer having an aromatic skeleton or an alicyclic skeleton and having a molecular weight of less than 1000; a plurality of conductive particles; and a thermal polymerization initiator. The viscosity of the conductive paste at 25 DEG C is from 5 Pa * s to 50 Pa * s (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive paste containing conductive particles, an RFID inlay using the conductive paste, and a method for producing the RFID inlay. In addition, the present invention relates to the use of the conductive paste for bonding chips and the use of the conductive paste for obtaining an RFID inlay. Background Art

[0002] RFID (Radio Frequency Identification) inlays that can send and receive data in a contactless manner are widely used in contactless RFID tags, contactless RFID cards, etc. In particular, RFID inlays in the UHF (Ultra High Frequency) band (860MHz to 960MHz) have attracted attention due to their long communication distance. RFID inlays in the UHF band are used in various products and applications such as commuter tickets, inventory management, logistics management, and history management.

[0003] In the RFID inlay, a conductive paste containing conductive particles and a binder resin is used to adhere and connect a chip having electrodes on its surface and a substrate having wiring (antenna pattern) on its surface.

[0004] In recent years, as electronic components using RFID inlays have become smaller, chips used in RFID inlays have also become smaller, and there is a need for a conductive paste that has high adhesiveness and can be arranged on wiring with higher precision.

[0005] The following Patent Document 1 discloses an adhesive that can be applied to electronic components. The adhesive is an acrylic adhesive composition comprising a free radical initiator having a 10-hour half-life temperature of 80°C or less, a vinylidene-containing oligomer, and at least one diluent. The adhesive can be cured quickly at low temperatures, and the adhesive can be used for more than 24 hours at room temperature. In Patent Document 1, urethane acrylate is described as an example of the vinylidene-containing oligomer.

[0006] Patent Document 2 below discloses a conductive adhesive comprising a polymerizable acrylic compound, an organic peroxide, and solder particles, wherein the one-minute half-life temperature of the organic peroxide is lower than the solidus temperature of the solder particles. Patent Document 2 describes urethane acrylate as an example of the polymerizable acrylic compound.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2006-144018

[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-124330 Summary of the invention

[0011] Technical problem solved by the invention

[0012] In the conventional adhesives (conductive pastes) described in Patent Documents 1 and 2, adhesion can be improved to a certain extent. However, the viscosity of carbamate (meth) acrylate is relatively high, so the viscosity of the conductive paste containing carbamate (meth) acrylate also becomes high, and it is difficult to configure the conductive paste on fine wiring with high precision. As a result, it is difficult to improve the conduction reliability of the obtained electronic components. In addition, when a low-viscosity material is added to carbamate (meth) acrylate in order to reduce the viscosity, the carbamate (meth) acrylate and the low-viscosity material cannot be evenly mixed, which sometimes reduces the conduction reliability.

[0013] Furthermore, in conventional conductive pastes, when a connection structure after conductive connection is left in a high-temperature and high-humidity environment for a long period of time (eg, 500 hours), the conduction reliability may be reduced.

[0014] An object of the present invention is to provide a conductive paste that can improve adhesion and conduction reliability. In addition, an object of the present invention is to provide an RFID inlay using the conductive paste and a method for producing the RFID inlay.

[0015] Technical means of solving problems

[0016] According to a broad scheme of the present invention, a conductive paste is provided, which includes a curable compound, a plurality of conductive particles and a thermal polymerization initiator, wherein the curable compound includes: a urethane (meth) acrylate having a molecular weight of 1000 or more and an aromatic skeleton, and a polymerizable monomer having a molecular weight of less than 1000 and an aromatic skeleton or an alicyclic skeleton, and the viscosity of the conductive paste at 25°C is 5 Pa·s or more and 50 Pa·s or less.

[0017] In a specific embodiment of the conductive paste of the present invention, the content of the conductive particles is 3 parts by weight or more and 30 parts by weight or less relative to 100 parts by weight of the curable compound in the conductive paste.

[0018] In a specific embodiment of the conductive paste of the present invention, the conductive particles have a particle diameter of 10 μm or less.

[0019] In a specific aspect of the conductive paste according to the present invention, the conductive particles include substrate particles and a conductive portion disposed on a surface of the substrate particles, and the conductive portion contains nickel.

[0020] In a specific embodiment of the conductive paste of the present invention, a cured product obtained by heating the conductive paste at 150° C. for 10 minutes has a storage elastic modulus at 25° C. of 0.7 GPa to 3.0 GPa.

[0021] In a specific embodiment of the conductive paste of the present invention, the conductive paste is applied to a substrate having a surface tension of 20 mN / m to 50 mN / m.

[0022] In a specific embodiment of the conductive paste of the present invention, the conductive paste is used to bond a flat surface with an area of ​​0.50 mm 2 The following chips.

[0023] In a specific embodiment of the conductive paste of the present invention, the conductive paste is used to obtain an RFID inlay.

[0024] According to a broad scheme of the present invention, an RFID inlay is provided, which comprises a substrate having wiring on its surface, a chip, and a bonding portion for bonding the substrate and the chip, wherein the material of the bonding portion is the conductive paste, and the wiring and the chip are electrically connected via the conductive particles in the bonding portion.

[0025] According to a broad scheme of the present invention, a method for manufacturing an RFID inlay is provided, which comprises: a first configuration step, in which the conductive paste is configured on the surface of a substrate having wiring on the surface; a second configuration step, in which a chip is configured on the surface of the conductive paste opposite to the substrate side; and a bonding step, in which the conductive paste is heated and pressurized to form a bonding portion for bonding the substrate and the chip through the conductive paste, and the wiring and the chip are electrically connected through the conductive particles in the bonding portion.

[0026] In a specific embodiment of the method for manufacturing an RFID inlay of the present invention, the substrate is in a long strip shape, and in the first arrangement step, the second arrangement step and the bonding step, the RFID inlay is manufactured by conveying the long strip substrate in a roll-to-roll manner.

[0027] According to a broad aspect of the present invention, there is provided a conductive paste for bonding a surface area of ​​0.50 mm 2 The following chips are used.

[0028] According to a broad aspect of the present invention, there is provided a use of the conductive paste for obtaining an RFID inlay.

[0029] Effects of the Invention

[0030] The conductive paste of the present invention comprises a curable compound, a plurality of conductive particles and a thermal polymerization initiator. In the conductive paste of the present invention, the curable compound comprises: a urethane (meth) acrylate having a molecular weight of 1000 or more and an aromatic skeleton, and a polymerizable monomer having a molecular weight of less than 1000 and an aromatic skeleton or an alicyclic skeleton. The viscosity of the conductive paste of the present invention at 25°C is 5 Pa·s or more and 50 Pa·s or less. In the conductive paste of the present invention, due to the above-mentioned structure, the adhesion can be improved and the conduction reliability can be improved. DETAILED DESCRIPTION

[0031] Hereinafter, the details of the present invention will be described.

[0032] (Conductive paste)

[0033] The conductive paste of the present invention comprises (A) a curable compound, a plurality of (B) conductive particles, and (C) a thermal polymerization initiator. In the conductive paste of the present invention, the curable compound comprises (A1) a urethane (meth) acrylate having a molecular weight of 1000 or more and an aromatic skeleton, and (A2) a polymerizable monomer having a molecular weight of less than 1000 and an aromatic skeleton or an alicyclic skeleton. The viscosity of the conductive paste of the present invention at 25° C. is 5 Pa·s or more and 50 Pa·s or less.

[0034] In the conductive paste of the present invention, since it has the above-mentioned structure, the adhesiveness can be improved. In addition, in the conductive paste of the present invention, since it has the above-mentioned structure, the conductive paste can be arranged on fine wiring with high precision, and as a result, the conduction reliability can be improved. In addition, in the conductive paste of the present invention, since it has the above-mentioned structure, the connection structure (electronic component) can maintain high conduction reliability even when it is left for a long time in a high temperature and high humidity environment.

[0035] In conventional conductive pastes, it is difficult to improve adhesion and conduction reliability, and to maintain high conduction reliability when the paste is left in a high-temperature and high-humidity environment for a long period of time.

[0036] The present inventors have found that the adhesiveness of a conductive paste can be improved and the conduction reliability can be improved by combining a specific urethane (meth)acrylate and a specific polymerizable monomer.

[0037] The conductive paste of the present invention is in a paste state at 25° C. The conductive paste is sprayed and used at, for example, 20° C. to 30° C.

[0038] The viscosity (η25) of the conductive paste at 25°C is preferably 6 Pa·s or more, more preferably 10 Pa·s or more, further preferably 15 Pa·s or more, preferably 48 Pa·s or less, more preferably 45 Pa·s or less, further preferably 40 Pa·s or less. When the viscosity (η25) is above the lower limit, the conductive paste can be suppressed from flowing out of the wiring. When the viscosity (η25) is below the upper limit, the conductive paste can be arranged on fine wiring with higher precision.

[0039] The viscosity (η25) can be measured, for example, using an E-type viscometer under the conditions of 25° C. and 5 rpm. Examples of the E-type viscometer include “TV22 Viscometer” manufactured by Toki Sangyo Co., Ltd.

[0040] The conductive paste has good adhesiveness and is suitable for use as an adhesive. The conductive paste is particularly suitable for bonding a substrate to a chip.

[0041] From the viewpoint of further improving the conduction reliability, the conductive paste is preferably an anisotropic conductive paste. The conductive paste is suitable for electrical connection of electrodes. The conductive paste is suitable for use in order to obtain a connection structure. The conductive paste is suitable for use in order to obtain an electronic component. The conductive paste is particularly suitable for use in order to obtain an RFID inlay (the purpose of the conductive paste for obtaining an RFID inlay). The conductive paste is suitable for bonding and connecting a chip having an electrode on its surface to a substrate having wiring (antenna pattern) on its surface (the purpose of the conductive paste for bonding and connecting a chip having an electrode on its surface to a substrate having wiring (antenna pattern) on its surface).

[0042] The conductive paste is preferably applied to a substrate having a surface tension of 20 mN / m to 50 mN / m (application of the conductive paste on a substrate having a surface tension of 20 mN / m to 50 mN / m). The conductive paste is particularly preferably applied to a substrate having a surface tension of 30 mN / m to 50 mN / m (application of the conductive paste on a substrate having a surface tension of 30 mN / m to 50 mN / m). The conductive paste is preferably used to bond a surface area of ​​0.50 mm 2 The following chips (for bonding surface area of ​​0.50mm 2 The following is the use of the conductive paste in the chip).

[0043] The conductive paste is preferably thermosetting, and is more preferably a thermosetting anisotropic conductive paste.

[0044] The storage modulus of the cured product obtained by heating the conductive paste at 150° C. for 10 minutes at 25° C. is preferably 0.7 GPa or more, more preferably 0.8 GPa or more, further preferably 1.0 GPa or more, particularly preferably 1.5 GPa or more, preferably 3.0 GPa or less, more preferably 2.8 GPa or less, further preferably 2.5 GPa or less. When the storage modulus of the cured product at 25° C. is above the lower limit and below the upper limit, the adhesiveness can be further improved, and the occurrence of cracks and warping in the bonding portion of the obtained connection structure can be effectively prevented.

[0045] The storage modulus of the cured product at 25° C. can be measured by a dynamic viscoelasticity measuring device (e.g., “DVA-200” manufactured by IT Keisoku Seigyo Co., Ltd.). For the measurement by the dynamic viscoelasticity measuring device, for example, the measurement sample cut into a size of 50 mm in length, 3 mm in width, and 1 mm in thickness of the cured product can be used, and the measurement can be performed under the conditions of a frequency of 10 Hz, a strain of 0.1%, and a stretching width and a clamping width of 20 mm.

[0046] It should be noted that, when the conductive paste of the present invention is actually used (for example, when the conductive paste is used to prepare a connection structure such as an RFID inlay), the curing conditions of the conductive paste may not require the heating conditions of 150° C. and 10 minutes.

[0047] Hereinafter, each component contained in the conductive paste will be described.

[0048] In the present specification, "(meth)acrylate" means acrylate and methacrylate. "(meth)acrylic" means acrylic and methacrylic. "(meth)acryloyl" means acryloyl and methacryloyl.

[0049] <(A) Curable Compound>

[0050] The conductive paste includes (A) a curable compound. The (A) curable compound includes the following components: (A1) a urethane (meth) acrylate having a molecular weight of 1000 or more and having an aromatic skeleton (hereinafter, "(A1) urethane (meth) acrylate"). (A2) a polymerizable monomer having a molecular weight of less than 1000 and having an aromatic skeleton or an alicyclic skeleton (hereinafter, "(A2) polymerizable monomer").

[0051] In 100 wt % of the conductive paste, the content of the (A) curable compound is preferably 15 wt % or more, more preferably 20 wt % or more, preferably 55 wt % or less, more preferably 50 wt % or less, further preferably 45 wt % or less, particularly preferably 40 wt % or less, and most preferably 35 wt % or less. When the content of the (A) curable compound is above the lower limit and below the upper limit, the adhesiveness can be further improved and the conduction reliability can be further improved.

[0052] In 100 wt % of the conductive paste, the total content of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer is preferably 20 wt % or more, and more preferably 25 wt % or more. In 100 wt % of the conductive paste, the total content of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer is preferably 75 wt % or less, more preferably 70 wt % or less, further preferably 65 wt % or less, particularly preferably 60 wt % or less, and most preferably 55 wt % or less. When the total content of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer is above the lower limit and below the upper limit, the viscosity of the conductive paste can be adjusted to a suitable range, the adhesion can be further improved, and the conduction reliability can be further improved.

[0053] In 100 wt % of the (A) curable compound, the total content of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer is preferably 20 wt % or more, more preferably 40 wt % or more, preferably 90 wt % or less, more preferably 80 wt % or less. When the total content of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer is above the lower limit and below the upper limit, the viscosity of the conductive paste can be adjusted to a suitable range, the adhesion can be further improved, and the conduction reliability can be further improved.

[0054] [(A1) Urethane (meth)acrylate]

[0055] The (A1) urethane (meth)acrylate has a molecular weight of 1000 or more and has an aromatic skeleton. The (A1) urethane (meth)acrylate is an aromatic urethane (meth)acrylate having a molecular weight of 1000 or more.

[0056] The (A1) carbamate (meth)acrylate has an aromatic skeleton, a carbamate bond and a (meth)acryloyl group. The (A1) carbamate (meth)acrylate may be a carbamate (meth)acrylate having one (meth)acryloyl group, or may be a carbamate (meth)acrylate having two or more (meth)acryloyl groups. The (A1) carbamate (meth)acrylate may be a monofunctional (meth)acrylate, a difunctional (meth)acrylate, a trifunctional (meth)acrylate, or a tetrafunctional or higher (meth)acrylate. The (A1) carbamate (meth)acrylate may have less than 100 (meth)acryloyl groups, less than 50, or less than 10.

[0057] Examples of the urethane (meth)acrylate (A1) include “CN973,” “CN978NS,” “CN992,” “CN9167,” “CN9782,” “CN9783,” “CN970,” “CN971,” “CN972,” “CN975NS,” and “CN9165” (manufactured by the aforementioned Sartomer), “UN-9200A,” “UN-9000PEP,” “UN-5500,” and “UN-5590” (manufactured by the aforementioned Negami Industries), “EBECRYL 210,” “EBECRYL 220” (manufactured by the aforementioned Daicelallnex), “GENOMER 4217” (manufactured by Rahn AG), and “SU704,” “SU710,” “SU720,” “SU7206,” “PSU537M2,” and “PSU537M10” (manufactured by the aforementioned Okajima Corporation).

[0058] In addition, the (A1) urethane (meth) acrylate can be obtained by, for example, the following method. A method of reacting a polyol compound, an isocyanate compound, and a (meth) acrylic acid derivative having an aromatic skeleton in the presence of a catalyst. A method of reacting a polyol compound having an aromatic skeleton, an isocyanate compound, and a (meth) acrylic acid derivative in the presence of a catalyst. A method of reacting a polyol compound having an aromatic skeleton and a (meth) acrylic acid derivative having an isocyanate group in the presence of a catalyst. A method of reacting an isocyanate compound having an aromatic skeleton and a (meth) acrylic acid derivative having a hydroxyl group in the presence of a catalyst.

[0059] The molecular weight of the urethane (meth)acrylate (A1) is preferably 1500 or more, more preferably 2000 or more, further preferably 3000 or more, particularly preferably 5000 or more, preferably 30000 or less, more preferably 25000 or less, further preferably 20000 or less, and particularly preferably 18000 or less. When the molecular weight of the urethane (meth)acrylate (A1) is above the lower limit and below the upper limit, the adhesiveness can be further improved, and the conduction reliability can be further improved.

[0060] With respect to the molecular weight of the (A1) carbamate (meth) acrylate, when the structural formula of the (A1) carbamate (meth) acrylate can be determined, it means the molecular weight that can be calculated from the structural formula. In addition, when the (A1) carbamate (meth) acrylate is a polymer whose structural formula cannot be determined, the molecular weight means the weight average molecular weight. The weight average molecular weight represents the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). The molecular weight of the (A1) carbamate (meth) acrylate is preferably the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). The weight average molecular weight can be measured by the following measuring device and measuring conditions.

[0061] Measurement equipment: "Waters GPC System (Waters 2690 + Waters 2414 (RI))" manufactured by Waters Corporation of Japan

[0062] Measurement conditions Column: Shodex GPC LF-G × 1, Shodex GPC LF-804 × 2

[0063] Mobile phase: THF 1.0mL / min

[0064] Sample concentration: 5 mg / mL

[0065] Detector: Differential Refractive Index Detector (RID)

[0066] Standard material: polystyrene (manufactured by TOSOH, weight average molecular weight: 620 to 590,000)

[0067] The viscosity of the urethane (meth)acrylate (A1) at 25°C is preferably 10 Pa·s or more, more preferably 50 Pa·s or more, further preferably 100 Pa·s or more, preferably 3000 Pa·s or less, more preferably 2500 Pa·s or less, further preferably 2000 Pa·s or less. When the viscosity of the urethane (meth)acrylate (A1) at 25°C is above the lower limit and below the upper limit, the adhesiveness can be further improved and the conduction reliability can be further improved.

[0068] The viscosity of the urethane (meth)acrylate (A1) at 25° C. can be measured, for example, using an E-type viscometer at 25° C. and 5 rpm. Examples of the E-type viscometer include “TV22 Viscometer” manufactured by Toki Sangyo Co., Ltd.

[0069] In 100 wt % of the conductive paste, the content of the (A1) urethane (meth) acrylate is preferably 15 wt % or more, more preferably 20 wt % or more, preferably 55 wt % or less, more preferably 50 wt % or less. When the total content of the (A1) urethane (meth) acrylate is above the lower limit and below the upper limit, the adhesiveness can be further improved and the conduction reliability can be further improved.

[0070] In 100 wt % of the (A) curable compound, the content of the (A1) urethane (meth) acrylate is preferably 15 wt % or more, more preferably 20 wt % or more, preferably 50 wt % or less, more preferably 45 wt % or less. When the total content of the (A1) urethane (meth) acrylate is above the lower limit and below the upper limit, the adhesiveness can be further improved and the conduction reliability can be further improved.

[0071] In the total of 100 wt % of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer, the content of the (A1) urethane (meth) acrylate is preferably 15 wt % or more, more preferably 20 wt % or more, preferably 70 wt % or less, more preferably 65 wt % or less. When the content of the (A1) urethane (meth) acrylate is above the lower limit and below the upper limit, the viscosity of the conductive paste can be adjusted to a suitable range, the adhesion can be further improved, and the conduction reliability can be further improved.

[0072] [(A2) polymerizable monomer]

[0073] The (A2) polymerizable monomer has a molecular weight of less than 1000 and has an aromatic skeleton or an alicyclic skeleton. The (A2) polymerizable monomer may have an aromatic skeleton, may have an alicyclic skeleton, or may have both an aromatic skeleton and an alicyclic skeleton. The (A2) polymerizable monomer may include a polymerizable monomer having an aromatic skeleton and a polymerizable monomer having an alicyclic skeleton. The (A2) polymerizable monomer is preferably a polymerizable monomer other than a carbamate (meth)acrylate having an aromatic skeleton, and more preferably a polymerizable monomer other than a carbamate (meth)acrylate. The (A2) polymerizable monomer is a polymerizable component that can be polymerized alone or copolymerized.

[0074] Examples of the polymerizable monomer having an aromatic skeleton include 2-phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, ethoxylated (4) nonylphenol (meth)acrylate, alkoxylated phenol (meth)acrylate, ethoxylated (3) bisphenol A (meth)diacrylate, ethoxylated (4) bisphenol A (meth)diacrylate, ethoxylated (10) bisphenol A (meth)diacrylate, and ethoxylated (30) bisphenol A (meth)diacrylate. From the viewpoint of improving compatibility with the (A1) urethane (meth)acrylate, the (A2) polymerizable monomer having an aromatic skeleton is preferably 2-phenoxyethyl (meth)acrylate or ethoxylated (3) bisphenol A (meth)diacrylate.

[0075] Examples of the polymerizable monomer having an alicyclic skeleton include cyclohexyl (meth)acrylate, dimethylol tricyclodecane di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, isobornyl (meth)acrylate, 4-tert-butylcyclohexanol, dicyclopentenyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, pentamethylpiperidinyl (meth)acrylate, tetramethylpiperidinyl (meth)acrylate, acryloylmorpholine, and 3,3,5-trimethylcyclohexyl (meth)acrylate. From the viewpoint of improving compatibility with the (A1) urethane (meth)acrylate, the (A2) polymerizable monomer having an alicyclic skeleton is preferably cyclohexyl (meth)acrylate or isobornyl (meth)acrylate.

[0076] The molecular weight of the polymerizable monomer (A2) is preferably 50 or more, more preferably 100 or more, further preferably 150 or more, particularly preferably 200 or more, and preferably 950 or less, more preferably 900 or less, further preferably 800 or less, and particularly preferably 700 or less. When the molecular weight of the polymerizable monomer (A2) is above the lower limit and below the upper limit, the compatibility with the urethane (meth)acrylate (A1) can be improved, the viscosity of the conductive paste can be adjusted to a suitable range, the adhesion can be further improved, and the conduction reliability can be further improved.

[0077] With respect to the molecular weight of the (A2) polymerizable monomer, when the structural formula of the (A2) polymerizable monomer can be determined, it means the molecular weight that can be calculated from the structural formula. In addition, in the case where the (A2) polymerizable monomer is a polymer whose structural formula cannot be determined, the molecular weight means the weight average molecular weight. The weight average molecular weight represents the weight average molecular weight in terms of polystyrene measured by gel permeation chromatography (GPC). Since the (A2) polymerizable monomer has a relatively small molecular weight, the structural formula can generally be determined. The weight average molecular weight can be measured under the following measuring device and measuring conditions.

[0078] Measurement equipment: "Waters GPC System (Waters 2690 + Waters 2414 (RI))" manufactured by Waters Corporation of Japan

[0079] Measurement conditions Column: Shodex GPC LF-G × 1, Shodex GPC LF-804 × 2

[0080] Mobile phase: THF 1.0mL / min

[0081] Sample concentration: 5 mg / mL

[0082] Detector: Differential Refractive Index Detector (RID)

[0083] Standard material: polystyrene (manufactured by TOSOH, weight average molecular weight: 620 to 590,000)

[0084] The viscosity of the polymerizable monomer (A2) at 25°C is preferably 5 Pa·s or more, more preferably 10 Pa·s or more, further preferably 15 Pa·s or more, preferably 50 Pa·s or less, more preferably 45 Pa·s or less, further preferably 40 Pa·s or less. When the viscosity of the polymerizable monomer (A2) at 25°C is above the lower limit and below the upper limit, the conductive paste can be arranged on fine wiring with higher precision and the wettability to the substrate can be improved.

[0085] The viscosity of the polymerizable monomer (A2) at 25° C. can be measured, for example, using an E-type viscometer at 25° C. and 5 rpm. Examples of the E-type viscometer include “TV22 Viscometer” manufactured by Toki Sangyo Co., Ltd.

[0086] In 100 wt % of the conductive paste, the content of the (A2) polymerizable monomer is preferably 10 wt % or more, more preferably 15 wt % or more, preferably 50 wt % or less, and more preferably 45 wt % or less. When the content of the (A2) polymerizable monomer is above the lower limit and below the upper limit, the compatibility with the (A1) carbamate (meth) acrylate can be improved, and the viscosity of the conductive paste can be adjusted to a suitable range, which can further improve the adhesion and further improve the conduction reliability. It should be noted that when the (A2) polymerizable monomer includes a polymerizable monomer having an aromatic skeleton and a polymerizable monomer having an alicyclic skeleton, the content of the (A2) polymerizable monomer represents the total content of the polymerizable monomer having an aromatic skeleton and the polymerizable monomer having an alicyclic skeleton.

[0087] In 100% by weight of the (A) curable compound, the content of the (A2) polymerizable monomer is preferably 10% by weight or more, more preferably 15% by weight or more, preferably 55% by weight or less, and more preferably 50% by weight or less. When the content of the (A2) polymerizable monomer is above the lower limit and below the upper limit, the compatibility with the (A1) urethane (meth) acrylate can be improved, and the viscosity of the conductive paste can be adjusted to a suitable range, which can further improve the adhesion and further improve the conduction reliability. It should be noted that when the (A2) polymerizable monomer includes a polymerizable monomer having an aromatic skeleton and a polymerizable monomer having an alicyclic skeleton, the content of the (A2) polymerizable monomer represents the total content of the polymerizable monomer having an aromatic skeleton and the polymerizable monomer having an alicyclic skeleton.

[0088] In the total of 100 wt % of the (A1) carbamate (meth) acrylate and the (A2) polymerizable monomer, the content of the (A2) polymerizable monomer is preferably 15 wt % or more, more preferably 20 wt % or more, preferably 55 wt % or less, and more preferably 50 wt % or less. When the content of the (A2) polymerizable monomer is above the lower limit and below the upper limit, the compatibility with the (A1) carbamate (meth) acrylate can be improved, and the viscosity of the conductive paste can be adjusted to a suitable range, which can further improve the adhesion and further improve the conduction reliability. It should be noted that when the (A2) polymerizable monomer includes a polymerizable monomer having an aromatic skeleton and a polymerizable monomer having an alicyclic skeleton, the content of the (A2) polymerizable monomer represents the total content of the polymerizable monomer having an aromatic skeleton and the polymerizable monomer having an alicyclic skeleton.

[0089] The (A) curable compound may contain curable compounds other than the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer. The (A) curable compound may contain urethane (meth) acrylate other than the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer. The (A) curable compound may contain polymerizable components (polymerizable monomers) other than the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer. The curable compounds (polymerizable components) other than the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer are not particularly limited. The curable compounds (polymerizable components) other than the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer may be monofunctional (meth) acrylates or multifunctional (meth) acrylates. The curable compound (polymerizable component) other than the (A1) urethane (meth)acrylate and the (A2) polymerizable monomer may be a difunctional (meth)acrylate, a trifunctional (meth)acrylate, or a tetrafunctional or higher (meth)acrylate. The curable compound (polymerizable component) other than the (A1) urethane (meth)acrylate and the (A2) polymerizable monomer may have 100 or less (meth)acryloyl groups, 50 or less, or 10 or less.

[0090] Examples of the monofunctional (meth)acrylate include 2-(2-ethoxyethoxy)ethyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, lauryl (meth)acrylate, isobutyl (meth)acrylate, isodecyl (meth)acrylate, isooctyl (meth)acrylate, octyl / decyl (meth)acrylate, tridecyl (meth)acrylate, nonyl (meth)acrylate, caprolactone (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolane-(meth)acrylate) and 1,2-dioxolane-1,3-dioxolane-2-methylpropane (meth)acrylate. 4-yl)methyl (meth)acrylate, (3-ethyloxetane-3-yl)methyl (meth)acrylate, methoxyethyl (meth)acrylate, methoxypolyethylene glycol (350) mono(meth)acrylate, methoxytriethylene glycol (meth)acrylate, alkoxylated tetrahydrofurfuryl (meth)acrylate, alkoxylated lauryl (meth)acrylate, dimethylacrylamide, diethylacrylamide, hydroxyethylacrylamide, dimethylaminopropylacrylamide, isopropylacrylamide, N-acryloyloxyethylhexahydrophthalimide, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate, etc.

[0091] Examples of the polyfunctional (meth)acrylate include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol (meth)acrylate, 1,9-nonanediol di(meth)acrylate, polyethylene glycol (200) di(meth)acrylate, tetraethylene glycol di(meth)acrylate, triethylene glycol (meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol (400) di(meth)acrylate, dipropylene glycol di(meth)acrylate, alkoxylated hexanediol di(meth)acrylate, and dodecanediol di(meth)acrylate. (meth)acrylate, polyethylene glycol (600) di(meth)acrylate, polypropylene glycol (700) (meth)acrylate, propoxylated (2) neopentyl glycol di(meth)acrylate, alkoxylated neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, Tris-(2-hydroxyethyl)isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate, ethoxylated (3) trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate. From the viewpoint of increasing the storage modulus of the cured product and further increasing the adhesiveness, the (A) curable compound preferably contains a curable compound (polymerizable component) other than the (A1) urethane (meth)acrylate and the (A2) polymerizable monomer. From the viewpoint of increasing the storage modulus of the cured product and further improving the adhesiveness, the curable compound (polymerizable component) other than the (A1) urethane (meth)acrylate and the (A2) polymerizable monomer preferably includes a polyfunctional curable compound, and more preferably includes a polyfunctional (meth)acrylate.

[0092] <(B) Conductive Particles>

[0093] The conductive paste contains a plurality of (B) conductive particles. The (B) conductive particles are not particularly limited. The (B) conductive particles may be solder particles or metal particles. The (B) conductive particles may include substrate particles and a conductive portion disposed on the surface of the substrate particles. From the viewpoint of further improving conduction reliability, the (B) conductive particles preferably include substrate particles and a conductive portion disposed on the surface of the substrate particles.

[0094] The particle size of the conductive particles (B) is preferably 0.1 μm or more, more preferably 1 μm or more, further preferably 3 μm or more, preferably 100 μm or less, more preferably 30 μm or less, further preferably 10 μm or less. When the particle size of the conductive particles (B) is above the lower limit and below the upper limit, the conduction reliability can be further improved.

[0095] The particle size of the conductive particles (B) is preferably an average particle size, more preferably a number average particle size. The average particle size of the conductive particles can be determined, for example, by observing 50 random conductive particles under an electron microscope or an optical microscope and calculating the average value of the particle size of each conductive particle, or by performing laser diffraction particle size distribution measurement.

[0096] In the (B) conductive particles, when the particle size of the conductive particles is measured by observing 50 arbitrary conductive particles under an electron microscope or an optical microscope, for example, it can be measured in the following manner. Add to "TECHNOVIT4000" manufactured by Kulzer Company in a manner such that the content of the conductive particles is 30% by weight, disperse it, and prepare an embedded resin body for conductive particle inspection. Use an ion milling device ("IM4000" manufactured by HITACHI HIGH-TECHNOLOGIES) in a manner such that it passes through the center of the conductive particles dispersed in the embedded resin body for inspection, and cut out the cross section of the conductive particles. In addition, using a field emission scanning electron microscope (FE-SEM), set the image magnification to 25,000 times, randomly select 50 conductive particles, and observe each conductive particle. Measure the circle equivalent diameter of each conductive particle, and take the arithmetic average as the particle size of the conductive particle.

[0097] The coefficient of variation (CV value) of the particle size of the conductive particles (B) is preferably 10% or less, more preferably 5% or less. When the coefficient of variation of the particle size of the conductive particles (B) is below the upper limit, the conduction reliability can be further improved. The lower limit of the coefficient of variation (CV value) of the particle size of the conductive particles (B) is not particularly limited. The coefficient of variation (CV value) of the particle size of the conductive particles (B) may be 0% or more, and may be 1% or more.

[0098] The coefficient of variation (CV value) can be measured in the following manner.

[0099] CV value (%) = (ρ / Dn) × 100

[0100] ρ: Standard deviation of particle size of conductive particles

[0101] Dn: average value of particle size of conductive particles

[0102] The shape of the conductive particles (B) is not particularly limited. The conductive particles (B) may be spherical, may be other than spherical, may be flat, and the like.

[0103] In 100 wt % of the conductive paste, the content of the conductive particles (B) is preferably 0.01 wt % or more, more preferably 0.1 wt % or more, preferably 80 wt % or less, more preferably 60 wt % or less, further preferably 40 wt % or less, particularly preferably 20 wt % or less, and most preferably 10 wt % or less. When the content of the conductive particles (B) is above the lower limit and below the upper limit, the conduction reliability can be further improved.

[0104] The content of the conductive particles (B) is preferably 2 parts by weight or more, more preferably 3 parts by weight or more, further preferably 5 parts by weight or more, and particularly preferably 7 parts by weight or more, relative to 100 parts by weight of the curable compound (A) in the conductive paste. The content of the conductive particles (B) is preferably 35 parts by weight or less, more preferably 30 parts by weight or less, further preferably 25 parts by weight or less, and particularly preferably 20 parts by weight or less, relative to 100 parts by weight of the curable compound (A) in the conductive paste. When the content of the conductive particles (B) in the conductive paste is above the lower limit and below the upper limit, the conduction reliability can be further improved.

[0105] The content of the conductive particles (B) is preferably 3 parts by weight or more, more preferably 5 parts by weight or more, and further preferably 7 parts by weight or more, relative to a total of 100 parts by weight of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer in the conductive paste. The content of the conductive particles (B) is preferably 30 parts by weight or less, more preferably 25 parts by weight or less, and further preferably 20 parts by weight or less, relative to a total of 100 parts by weight of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer in the conductive paste. When the content of the conductive particles (B) is above the lower limit and below the upper limit, the conduction reliability can be further improved.

[0106] When the conductive particles (B) are metal particles, the metal of the metal particles includes silver, copper, nickel, silicon, gold, titanium, and alloys such as solder. From the viewpoint of further effectively improving the conduction reliability, the material of the metal particles preferably includes nickel or a nickel alloy, and the material of the metal particles is more preferably nickel or a nickel alloy. From the viewpoint of further effectively improving the conduction reliability, the outer surface portion of the metal particles preferably includes nickel or a nickel alloy.

[0107] Hereinafter, the electroconductive particle provided with the substrate particle and the electroconductive part arrange|positioned on the surface of the said substrate particle is demonstrated in detail.

[0108] (Base material particles)

[0109] As the substrate particles, resin particles, inorganic particles other than metal particles, organic-inorganic hybrid particles and metal particles can be cited. The substrate particles are preferably substrate particles other than metal particles, more preferably resin particles, inorganic particles other than metal particles or organic-inorganic hybrid particles. The substrate particles can be core-shell particles having a core and a shell disposed on the surface of the core. The core can be an organic core, and the shell can be an inorganic shell.

[0110] The substrate particles are more preferably resin particles or organic-inorganic hybrid particles, and may be resin particles or organic-inorganic hybrid particles. By using these preferred substrate particles, the effects of the present invention can be more effectively exerted.

[0111] As the material of the resin particles, various resins can be suitably used. As the material of the resin particles, polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene can be cited; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polyalkylene terephthalate, polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenolic resin, melamine resin, benzoguanamine resin, urea formaldehyde resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polysulfone, polyphenylene ether, polyacetal, polyimide, polyamideimide, polyetheretherketone, polyethersulfone, divinylbenzene polymer, and polymers obtained by polymerizing one or more polymerizable monomers having ethylenically unsaturated groups, etc. The divinylbenzene polymer can be a divinylbenzene copolymer. Examples of the divinylbenzene-based copolymer include divinylbenzene-styrene copolymers and divinylbenzene-(meth)acrylate copolymers.

[0112] From the perspective of being able to design and synthesize resin particles having arbitrary compression characteristics suitable for the conductive paste and easily controlling the hardness of the resin particles within an appropriate range, the material of the resin particles is preferably a polymer obtained by polymerizing one or more polymerizable monomers having multiple ethylenically unsaturated groups.

[0113] When the resin particles are obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, examples of the polymerizable monomer having an ethylenically unsaturated group include non-crosslinking monomers and crosslinking monomers.

[0114] Examples of the non-crosslinking monomer include styrene monomers such as styrene and α-methylstyrene; carboxyl-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride; and alkyl (meth)acrylate compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. ; (meth)acrylate compounds containing oxygen atoms such as 2-hydroxyethyl (meth)acrylate, glyceryl (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; unsaturated hydrocarbons such as ethylene, propylene, isoprene, and butadiene; halogen-containing monomers such as trifluoromethyl (meth)acrylate, pentafluoroethyl (meth)acrylate, vinyl chloride, vinyl fluoride, and chlorostyrene, etc.

[0115] Examples of the crosslinking monomer include polyfunctional (meth)acrylate compounds such as tetramethylolmethane tetra(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, (poly)tetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; and silane-containing monomers such as triallyl (iso)cyanurate, triallyl trimellitic acid, divinylbenzene, diallyl phthalate, diallyl acrylamide, diallyl ether, γ-(meth)acryloxypropyltrimethoxysilane, trimethoxysilylstyrene, and vinyltrimethoxysilane.

[0116] The resin particles can be obtained by polymerizing the polymerizable monomer having an ethylenically unsaturated group by a known method, such as a suspension polymerization method in the presence of a free radical polymerization initiator, and a method of using non-crosslinked seed particles to swell the free radical polymerization initiator together with the monomer to polymerize.

[0117] When the substrate particles are inorganic particles other than metal particles or organic-inorganic hybrid particles, the inorganic material of the substrate particles includes silicon dioxide, aluminum oxide, barium titanate, zirconium oxide, and carbon black. The inorganic material is preferably not a metal. The particles formed by the silicon dioxide are not particularly limited, and for example, particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form cross-linked polymer particles and then firing as required can be cited. As the organic-inorganic hybrid particles, for example, organic-inorganic hybrid particles obtained by cross-linking an alkoxysilyl polymer and an acrylic resin can be cited.

[0118] The organic-inorganic hybrid particles are preferably core-shell organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. From the viewpoint of further effectively reducing the connection resistance between electrodes, the substrate particles are preferably organic-inorganic hybrid particles having an organic core and an inorganic shell disposed on the surface of the organic core.

[0119] Examples of the material of the organic core include the material of the resin particles described above.

[0120] As the material of the inorganic shell, the inorganic substances mentioned as the material of the substrate particles can be cited. The material of the inorganic shell is preferably silicon dioxide. The inorganic shell is preferably formed by firing the shell after metal alkoxide is made into a shell-like object by a sol-gel method on the surface of the core. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed by silane alkoxide.

[0121] When the substrate particles are metal particles, examples of the metal used as the material of the metal particles include silver, copper, nickel, silicon, gold, titanium, and alloys such as solder.

[0122] The particle size of the substrate particles is preferably 0.05 μm or more, more preferably 0.01 μm or more, further preferably 0.5 μm or more, further preferably 1 μm or more, particularly preferably 3 μm or more, preferably 50 μm or less, more preferably 30 μm or less, further preferably 20 μm or less, and particularly preferably 10 μm or less. When the particle size of the substrate particles is above the lower limit, the conduction reliability becomes higher. In addition, when the conductive portion is formed on the surface of the substrate particles, it becomes difficult to condense and it becomes difficult to form condensed conductive particles. When the particle size of the substrate particles is below the upper limit, the conductive particles are easily fully compressed, and the connection resistance between the electrodes connected by the conductive particles can be further effectively reduced.

[0123] The particle size of the substrate particles is preferably an average particle size, more preferably a number average particle size. The number average particle size of the substrate particles can be measured, for example, in the following manner. In such a manner that the content of the conductive particles is 30% by weight, it is added to "TECHNOVIT4000" manufactured by Kulzer Company, dispersed, and an embedded resin body for conductive particle inspection is prepared. An ion milling device (HITACHI HIGH-TECHNOLOGIES "IM4000") is used to cut out the cross section of the conductive particles in the conductive particles embedded in the resin body for inspection so as to be dispersed near the center of the substrate particles. In addition, a field emission scanning electron microscope (FE-SEM) is used, the image magnification is set to 25,000 times, 50 conductive particles are randomly selected, and the substrate particles of each conductive particle are observed. The particle size of the substrate particles in each conductive particle is measured, and the arithmetic average is taken as the average particle size of the substrate particles.

[0124] (Conductive part)

[0125] The conductive portion preferably comprises a metal. The metal constituting the conductive portion is not particularly limited. As the metal, for example, gold, silver, copper, platinum, palladium, zinc, lead, aluminum, cobalt, indium, ruthenium, nickel, chromium, titanium, antimony, bismuth, germanium and cadmium, and alloys thereof, etc. can be cited. In addition, as the metal, tin-doped indium oxide (ITO) can be used. The metal can be used only one or in combination of two or more. From the viewpoint of further reducing the connection resistance between the electrodes, it is preferably an alloy containing tin, nickel, palladium, ruthenium, silver, copper or gold, and more preferably nickel or palladium.

[0126] From the viewpoint of further effectively improving conduction reliability, the conductive portion preferably includes nickel, and more preferably the outer surface portion of the conductive portion includes nickel.

[0127] The content of nickel in 100 wt % of the conductive portion containing nickel is preferably 10 wt % or more, more preferably 50 wt % or more, further preferably 60 wt % or more, further preferably 70 wt % or more, and particularly preferably 90 wt % or more. The content of nickel in 100 wt % of the conductive portion containing nickel may be 99 wt % or less, 90 wt % or less, or 70 wt % or less.

[0128] The conductive portion may be formed from a single layer. The conductive portion may be formed from multiple layers. That is, the conductive portion may have a laminated structure of more than two layers. When the conductive portion is formed from multiple layers, the metal constituting the outermost layer is preferably gold, silver, nickel, palladium, ruthenium, copper or an alloy containing tin, more preferably nickel. When the metal constituting the outermost layer is one of these preferred metals, the connection resistance between the electrodes becomes further lower.

[0129] The method for forming the conductive portion on the surface of the substrate particles is not particularly limited. As the method for forming the conductive portion, for example, a method based on electroless plating, a method based on electroplating, a method based on physical collision, a method based on a mechanochemical reaction, a method based on physical evaporation or physical adsorption, and a method of applying a metal powder or a paste comprising a metal powder and an adhesive to the surface of the substrate particles, etc. can be cited. The method for forming the conductive portion is preferably a method based on electroless plating, electroplating or physical collision. As the method based on physical evaporation, methods such as vacuum evaporation, ion plating and ion sputtering can be cited. In addition, in the method based on physical collision, for example, THETACOMPOSER (TOKUJU company system) is used.

[0130] The thickness of the conductive portion is preferably 0.005 μm or more, more preferably 0.01 μm or more, preferably 10 μm or less, more preferably 1 μm or less, and further preferably 0.3 μm or less. When the thickness of the conductive portion is above the lower limit and below the upper limit, sufficient conductivity can be obtained, and the conductive particles will not become too hard, and the conductive particles can be sufficiently deformed during connection.

[0131] When the conductive portion is formed of multiple layers, the thickness of the conductive portion of the outermost layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, preferably 0.5 μm or less, and more preferably 0.1 μm or less. When the thickness of the conductive portion of the outermost layer is above the lower limit and below the upper limit, the conductive portion of the outermost layer becomes uniform, the corrosion resistance becomes sufficiently high, and the connection resistance between the electrodes can be sufficiently reduced.

[0132] The thickness of the conductive portion can be measured, for example, by observing a cross section of the conductive particle using a transmission electron microscope (TEM).

[0133] Core material:

[0134] The (B) conductive particles preferably have a plurality of protrusions on the outer surface of the conductive portion. An oxide film is often formed on the surface of the electrode connected by the (B) conductive particles. When the (B) conductive particles having protrusions on the surface of the conductive portion are used, the oxide film can be effectively removed by arranging the (B) conductive particles between the electrodes and pressing them together. Therefore, the electrode and the conductive portion are further reliably in contact, and the connection resistance between the electrodes is further reduced. In addition, when connecting the electrodes, the filler between the (B) conductive particles and the electrode can be effectively removed by the protrusions of the (B) conductive particles. Therefore, the conduction reliability between the electrodes becomes higher.

[0135] As a method for forming the protrusion, there can be cited a method of forming a conductive portion by electroless plating after attaching a core material to the surface of a substrate particle, and a method of forming a conductive portion by electroless plating on the surface of a substrate particle after forming a conductive portion by electroless plating, attaching a core material, and further forming a conductive portion by electroless plating, etc. In addition, in order to form a protrusion, the core material is not used, and a method of forming a conductive portion by electroless plating on the surface of the conductive portion in a protrusion shape can be used.

[0136] As a method for attaching the core material to the surface of the substrate particles, for example, a method of adding the core material to the dispersion of the substrate particles, accumulating and attaching the core material to the surface of the substrate particles by van der Waals force, and adding the core material to a container to which the substrate particles are added, and attaching the core material to the surface of the substrate particles by mechanical action based on the rotation of the container, etc. From the viewpoint of controlling the amount of the attached core material, the method for attaching the core material to the surface of the substrate particles is preferably a method for attaching the core material to the surface of the substrate particles in the dispersion.

[0137] As the material constituting the core material, conductive materials and non-conductive materials can be cited. As the conductive material, for example, conductive non-metals such as metals, metal oxides, graphite, and conductive polymers can be cited. As the conductive polymer, polyacetylene can be cited. As the non-conductive material, silicon dioxide, aluminum oxide, titanium oxide, tungsten carbide, zirconium oxide, etc. can be cited. From the viewpoint of further improving the conduction reliability between electrodes, the core material is preferably a metal.

[0138] The metal is not particularly limited. As the metal, for example, metals such as gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium and cadmium, and alloys consisting of two or more metals such as tin-lead alloy, tin-copper alloy, tin-silver alloy, tin-lead-silver alloy and tungsten carbide can be cited. From the viewpoint of further improving the conduction reliability between electrodes, the metal is preferably nickel, copper, silver or gold. The metal may be the same as or different from the metal constituting the conductive portion.

[0139] The shape of the core material is not particularly limited. The shape of the core material is preferably a block. Examples of the core material include a particle-shaped block, an aggregated block of a plurality of fine particles, and an indefinite-shaped block.

[0140] The particle size (average particle size) of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, preferably 0.9 μm or less, more preferably 0.2 μm or less. When the particle size of the core material is above the lower limit and below the upper limit, the connection resistance between electrodes can be effectively reduced.

[0141] The particle size of the core material is preferably an average particle size, more preferably a number average particle size. The particle size of the core material can be determined, for example, by observing 50 arbitrary core materials under an electron microscope or an optical microscope, calculating the average value of the particle size of each core material, or performing laser diffraction particle size distribution measurement.

[0142] <(C) Thermal Polymerization Initiator>

[0143] The conductive paste includes (C) a thermal polymerization initiator. The (C) thermal polymerization initiator is a compound that can start polymerization by heating.

[0144] Since the conductive paste contains the (C) thermal polymerization initiator, the polymerizable components in the conductive paste can be polymerized by heating. Since the conductive paste contains the (C) thermal polymerization initiator, the polymerization of the (A1) urethane (meth)acrylate and the (A2) polymerizable monomer can be initiated by heating.

[0145] In the conductive paste, the (A1) carbamate (meth) acrylate and the (A2) polymerizable monomer may be copolymerized by heating, or may be polymerized separately. In the conductive paste, a homopolymer of the (A1) carbamate (meth) acrylate may be formed by heating, a homopolymer of the (A2) polymerizable monomer may be formed, or a copolymer of the (A1) carbamate (meth) acrylate and the (A2) polymerizable monomer may be formed. From the viewpoint of further improving adhesion and further improving conduction reliability, it is preferred to form a copolymer of the (A1) carbamate (meth) acrylate and the (A2) polymerizable monomer by heating.

[0146] The (C) thermal polymerization initiator preferably comprises a thermal free radical polymerization initiator, preferably a thermal free radical polymerization initiator. Examples of the thermal free radical polymerization initiator include peroxide-based free radical polymerization initiators, azo-based free radical polymerization initiators, and redox-based free radical polymerization initiators. The (C) thermal polymerization initiator may be used alone or in combination of two or more.

[0147] Examples of the azo radical polymerization initiator include azobisisobutyronitrile, azobiscyclohexanecarbonitrile, and azobisdimethylvaleronitrile.

[0148] As the peroxide free radical polymerization initiator, diacyl free radical polymerization initiator, peroxyester free radical polymerization initiator, dialkyl free radical polymerization initiator, percarbonate free radical polymerization initiator and ketone peroxide free radical polymerization initiator etc. can be mentioned. As the diacyl free radical polymerization initiator, lauroyl peroxide and benzoyl peroxide etc. can be mentioned. As the peroxyester free radical polymerization initiator, tert-butyl perbenzoate, tert-butyl peroxyacetate, tert-butyl peroxypivalate and tert-butyl peroxy-2-ethylhexanoate etc. can be mentioned. As the dialkyl free radical polymerization initiator, diisopropyl peroxide and di-tert-butyl peroxide etc. can be mentioned. As the percarbonate free radical polymerization initiator, diisopropyl peroxydicarbonate etc. can be mentioned. As the ketone peroxide free radical polymerization initiator, methyl ethyl ketone peroxide etc. can be mentioned.

[0149] The redox free radical polymerization initiator comprises, for example, a peroxide and a reducing agent or a metal-containing compound. Specific examples of the redox free radical polymerization initiator include a mixture of benzoyl peroxide and an organic amine, a mixture of the peroxyester free radical polymerization initiator and a reducing agent such as a thiol, and a mixture of methyl ethyl ketone peroxide and an organic cobalt salt.

[0150] From the viewpoint of improving reactivity and storage stability, the (C) thermal polymerization initiator preferably contains a peroxide-based radical polymerization initiator.

[0151] From the viewpoint of improving reactivity and storage stability, the content of the (C) thermal polymerization initiator in 100 wt % of the conductive paste is preferably 0.1 wt % or more, more preferably 0.3 wt % or more, further preferably 0.5 wt % or more, preferably 5 wt % or less, more preferably 4 wt % or less, further preferably 3 wt % or less.

[0152] The content of the (C) thermal polymerization initiator is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and further preferably 0.7 parts by weight or more, and preferably 6 parts by weight or less, more preferably 5 parts by weight or less, and further preferably 4 parts by weight or less, relative to 100 parts by weight of the (A) curable compound in the conductive paste. When the content of the (C) thermal polymerization initiator is above the lower limit and below the upper limit, reactivity and storage stability can be improved.

[0153] The content of the (C) thermal polymerization initiator is preferably 0.4 parts by weight or more, more preferably 0.6 parts by weight or more, and further preferably 0.8 parts by weight or more, relative to 100 parts by weight of the total of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer in the conductive paste. The content of the (C) thermal polymerization initiator is preferably 8 parts by weight or less, more preferably 7 parts by weight or less, and further preferably 6 parts by weight or less, relative to 100 parts by weight of the total of the (A1) urethane (meth) acrylate and the (A2) polymerizable monomer in the conductive paste. When the content of the (C) thermal polymerization initiator is above the lower limit and below the upper limit, reactivity and storage stability can be improved.

[0154] <Other ingredients>

[0155] The conductive paste may contain ingredients other than the curable compound (A), the plurality of conductive particles (B) and the thermal polymerization initiator (C). The conductive paste may contain other ingredients such as a solvent, a photopolymerization initiator, an inorganic filler, an organic filler, a colorant, an inhibitor, a chain transfer agent, an antioxidant, an ultraviolet absorber, a defoamer, a leveling agent, a surfactant, a slip agent, an antiblocking agent, a wax, a masking agent, a deodorant, a fragrance, a preservative, an antibacterial agent, an antistatic agent and an adhesion-imparting agent.

[0156] (Application of Conductive Paste)

[0157] The present invention is used for bonding the conductive paste with a surface area of ​​0.50 mm 2 The following are uses of the chip. In the use of the present invention, since a specific conductive paste and a chip with a specific plane area are used, the adhesion (between the substrate and the chip) can be improved, and the conduction reliability can be improved.

[0158] From the viewpoint of further improving the adhesion (between the substrate and the chip) and further improving the conduction reliability, the plane area of ​​the chip is preferably 0.04 mm 2 More preferably 0.09 mm 2 More preferably, 0.16 mm 2 Above, preferably 0.50mm 2 Below, more preferably 0.40 mm 2 Below, more preferably 0.30 mm 2 the following.

[0159] In addition, the use of the present invention is the use of the conductive paste to obtain an RFID inlay. In the use of the present invention, since a specific conductive paste is used, the adhesion (between the substrate and the chip) can be improved, and the conduction reliability can be improved.

[0160] (RFID inlay and method for manufacturing the RFID inlay)

[0161] The RFID inlay of the present invention comprises a substrate having wiring on its surface, a chip, and an adhesive portion for bonding the substrate and the chip. In the RFID inlay of the present invention, the material of the adhesive portion is the conductive paste. In the RFID inlay of the present invention, the wiring and the chip are electrically connected via the conductive particles in the adhesive portion.

[0162] The manufacturing method of the RFID inlay of the present invention comprises the following steps (1) to (3). (1) A first configuration step, which configures the conductive paste on the surface of a substrate having wiring on the surface. (2) A second configuration step, which configures a chip on the surface of the conductive paste opposite to the substrate side. (3) A bonding step, which heats and pressurizes the conductive paste to form a bonding portion that bonds the substrate and the chip with the conductive paste, and electrically connects the wiring and the chip with the conductive particles in the bonding portion.

[0163] In the RFID inlay and the method for manufacturing the RFID inlay of the present invention, since a specific conductive paste is used, the adhesion between the substrate and the chip can be improved, and the conduction reliability can be improved.

[0164] In the manufacturing method of the RFID inlay, the substrate is preferably in a long strip shape, and the RFID inlay is manufactured by conveying the long strip substrate in a roll-to-roll manner in the first configuration step, the second configuration step, and the bonding step. In this case, a plurality of RFID inlays can be manufactured continuously, and the manufacturing efficiency of the RFID inlay can be further improved.

[0165] When a roll-to-roll method is used, the conveyance speed of the substrate is not particularly limited.

[0166] Examples of a method for disposing the conductive paste include coating with a dispenser, screen printing, and discharge with an inkjet device.

[0167] The heating temperature in the bonding step is preferably 100° C. or higher, more preferably 150° C. or higher, preferably 400° C. or lower, more preferably 300° C. or lower, and further preferably 250° C. or lower. When the heating temperature in the bonding step is above the lower limit and below the upper limit, the electrical connection between the chip and the antenna can be improved.

[0168] The pressurizing pressure in the bonding step is preferably 0.5 N or more, more preferably 1 N or more, preferably 3.5 N or less, more preferably 3 N or less, and further preferably 2.5 N or less. When the pressurizing pressure in the bonding step is above the lower limit and below the upper limit, the electrical connection between the chip and the antenna can be improved.

[0169] The heating and pressurizing time in the bonding step is not particularly limited, and may be 5 seconds or longer, 15 seconds or shorter, or 10 seconds or shorter.

[0170] The RFID inlay can be cut into a given size as needed, or it can be cut for use. Preferably, on the long strip substrate, the plurality of chips are bonded by the plurality of bonding portions. On the long strip substrate, a stack of the plurality of chips and the bonding portions can be arranged. In the first arrangement step, the conductive paste is preferably arranged at a plurality of positions on the surface of the long strip substrate. In the second arrangement step, a plurality of chips are preferably used, and the chips are arranged on the surface opposite to the substrate side of the conductive paste arranged at a plurality of positions. After the chips are bonded to the long strip substrate by the bonding portions, the long strip substrate can be cut.

[0171] The substrate is not particularly limited. The substrate is preferably a circuit substrate. Examples of the circuit substrate include resin films, flexible printed circuit boards, rigid flexible substrates, glass substrates, and paper substrates. The substrate may be a resin substrate, a glass substrate, or a paper substrate.

[0172] The substrate has wiring (antenna pattern) on the surface. The wiring (antenna pattern) is formed on the surface of the base material. The substrate preferably has a base material and wiring (antenna pattern) arranged on the surface of the base material.

[0173] As the material of the substrate, resin, glass, paper, etc. can be cited. As the resin, PET (polyethylene terephthalate), PP (polypropylene), PVC (polyvinyl chloride), etc. can be cited. As for the paper, it can be impregnated with epoxy resin or phenolic resin. From the viewpoint of further improving the adhesiveness and manufacturing the RFID inlay by a roll-to-roll method, the material of the substrate is preferably resin or paper, and more preferably PET (polyethylene terephthalate) or paper. The substrate can be resin, glass, or paper.

[0174] Examples of the wiring (antenna pattern) include gold wiring, nickel wiring, tin wiring, aluminum wiring, silver wiring, SUS wiring, copper wiring, molybdenum wiring, and tungsten wiring. From the viewpoint of improving the operating sensitivity in the UHF band (860 MHz to 920 MHz), the wiring is preferably aluminum wiring.

[0175] From the viewpoint of suppressing thermal deformation of the substrate when mounting a chip (eg, IC chip) and improving flexibility, the thickness of the substrate is preferably greater than 20 μm, more preferably greater than 30 μm, preferably less than 200 μm, more preferably less than 100 μm.

[0176] The shapes of the substrate and the base material are not particularly limited. From the perspective of manufacturing the RFID inlay by a roll-to-roll method, the substrate and the base material are preferably in a long strip shape. The length of the substrate and the base material is not particularly limited. The length of the substrate and the base material may be greater than 1 m, greater than 10 m, less than 5000 m, or less than 1000 m.

[0177] The surface tension of the substrate (base material) is preferably 20 mN / m or more, more preferably 30 mN / m or more, further preferably 32 mN / m or more, particularly preferably 34 mN / m or more, preferably 50 mN / m or less, more preferably 48 mN / m or less, and further preferably 45 mN / m or less. When the surface tension of the substrate (base material) is above the lower limit and below the upper limit, the adhesiveness can be further improved. The conductive paste of the present invention can be suitably used for coating on a substrate (base material) having a surface tension above the lower limit and below the upper limit.

[0178] The surface tension of the substrate (base material) can be measured by the following method based on JIS K6768. A cotton swab is soaked with a JIS specified liquid and applied to the substrate (base material). The surface tension is determined from the shape of the coating film 2 seconds after the application.

[0179] Examples of the chip include semiconductor chips (IC chips) and the like.

[0180] The chip preferably has an electrode on the surface. As the electrode, metal electrodes such as a gold electrode, a nickel electrode, a tin electrode, an aluminum electrode, a silver electrode, a SUS electrode, a copper electrode, a molybdenum electrode and a tungsten electrode can be cited. From the viewpoint of further improving the conduction reliability, the electrode is preferably a copper electrode or a gold electrode, more preferably a copper electrode.

[0181] The number of the electrodes per chip is not particularly limited, and may be 1 or more, 4 or more, 20 or less, or 10 or less.

[0182] The shape of the chip is not particularly limited, and the shape of the chip can be rectangular, triangular, or circular.

[0183] The planar area of ​​the chip is preferably 0.04 mm 2More preferably 0.09 mm 2 More preferably, 0.16 mm 2 Above, preferably 0.50mm 2 Below, more preferably 0.40 mm 2 Below, more preferably 0.30 mm 2 When the planar area of ​​the chip is above the lower limit, the conductive paste can be placed on fine wiring with high precision. When the planar area of ​​the chip is below the upper limit, the RFID inlay can maintain the conduction reliability when placed in a high temperature and high humidity environment for a long time. The conductive paste of the present invention can be suitably used for bonding relatively small chips.

[0184] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples. The present invention is not limited to the following Examples.

[0185] The following materials were prepared.

[0186] (A1) Urethane (meth)acrylate:

[0187] UN-9200A (manufactured by Negami Industries, molecular weight (weight average molecular weight): 15,000, viscosity: 1,900,000 mPa·s)

[0188] (A2) polymerizable monomer:

[0189] 2-Phenoxyethyl acrylate (polymerizable monomer having an aromatic skeleton, molecular weight: 192, viscosity: 10 mPa·s)

[0190] Isobornyl acrylate (polymerizable monomer with an alicyclic skeleton, molecular weight: 208, viscosity: 9 mPa·s)

[0191] Curable compounds other than (A1) and (A2):

[0192] UN-6306 (manufactured by Negami Industries, urethane (meth)acrylate having no aromatic skeleton, molecular weight (weight average molecular weight): 6500, viscosity: 190000 mPa·s)

[0193] DPHA NS (manufactured by Sartomer, a polymerizable monomer having neither an aromatic skeleton nor an alicyclic skeleton, molecular weight (weight average molecular weight): 547, viscosity: 7800 mPa·s)

[0194] X-22-164 (manufactured by Shin-ET Susilicon Co., Ltd., a polymerizable monomer having neither an aromatic skeleton nor an alicyclic skeleton, molecular weight (weight average molecular weight): 390, viscosity: 55 mPa·s)

[0195] (B) Conductive particles:

[0196] NIELB-005-S (manufactured by Sekisui Chemical Co., Ltd., conductive particles comprising substrate particles and a conductive portion disposed on the surface of the substrate particles, content of nickel in 100% by weight of the conductive portion: 52% by weight, average particle size: 5 μm)

[0197] CN050 (manufactured by NIKKO-RICA, metal particles (nickel particles), average particle size: 5 μm)

[0198] AG6-11 (manufactured by DOWA ELECTRONICS, metal particles (silver particles), average particle size: 5 μm)

[0199] (C) Thermal polymerization initiator:

[0200] NOF Corporation's "PEROYL L"

[0201] Other Ingredients:

[0202] Silica (PM-20L manufactured by TOKUYAMA)

[0203] chip:

[0204] IC chip (copper electrode, NXP "UCODE7", plane area: 0.22mm 2 )

[0205] Substrate:

[0206] PET film ("PET" in the table, long strip, resin film with aluminum wiring whose operating frequency is UHF band (860MHz~920MHz), surface tension: 43mN / m)

[0207] PP film ("PP" in the table, long strip, resin film with aluminum wiring whose operating frequency is UHF band (860MHz~920MHz), surface tension: 22mN / m)

[0208] (Example 1)

[0209] (1) Preparation of conductive paste

[0210] The materials shown in Table 1 below were blended in the blending amounts shown in Table 1 below, and stirred using a planetary stirring device ("AWATORI Rentaro" manufactured by THINKY Corporation) to obtain a conductive paste (anisotropic conductive paste).

[0211] (2) Preparation of RFID Inlay

[0212] On the PET film, the obtained conductive paste is applied by a dispensing method to form a conductive paste layer (adhesive layer) (first configuration step). Next, on the surface of the conductive paste layer (adhesive layer) opposite to the substrate (base material) side, the IC chip is stacked in such a way that the wiring on the surface of the PET film and the electrodes on the surface of the chip are opposite to each other (second configuration step). Then, heat pressing is performed under the conditions of an upper heating tool of 180°C, a lower heating tool of 175°C, a pressure of 2N, and a pressing time of 7 seconds to solidify the conductive paste layer (adhesive layer) and form an adhesive portion. In addition, the wiring on the surface of the PET film and the electrodes on the surface of the chip are electrically connected through the conductive particles in the adhesive portion to obtain a connected structure (adhesive step). It should be noted that the first configuration step, the second configuration step, and the bonding step are performed using "DDA40000" manufactured by Muhlbauer. The obtained connection structure was cut into a size of 5 cm×1.5 cm using “DCL30000” manufactured by Muhlbauer, thereby obtaining an RFID inlay.

[0213] (Examples 2 to 8 and Comparative Examples 1 to 4)

[0214] A conductive paste and an RFID inlay were obtained in the same manner as in Example 1 except that the blending components and content of the conductive paste and the type of substrate (base material) were changed as shown in Tables 1 to 3.

[0215] (evaluate)

[0216] (1) Viscosity at 25°C

[0217] The viscosity of the obtained conductive paste at 25° C. was measured using an E-type viscometer (“TV22 Viscometer” manufactured by Toki Sangyo Co., Ltd.) at 25° C. and 5 rpm. The conductive paste obtained in Comparative Example 2 was not uniformly mixed, so the viscosity could not be measured.

[0218] (2) Adhesion (storage modulus)

[0219] The obtained conductive paste was heated at 150°C for 10 minutes to prepare a measurement sample A (cured product) having a length of 10 mm, a width of 1 mm to 10 mm, and a thickness of 15 mm to 50 mm. The storage modulus of the measurement sample A at 25°C was measured by the above method. The adhesion (storage modulus) was determined based on the storage modulus of the obtained cured product at 25°C according to the following criteria. It should be noted that the conductive paste obtained by Comparative Example 2 was not uniformly mixed, so the storage modulus could not be measured.

[0220] [Criteria for Determination of Adhesion (Storage Modulus)]

[0221] ○○: Storage modulus is 1.5 GPa or more and 3.0 GPa or less

[0222] ○: Storage modulus is 0.7 GPa or more and less than 1.5 GPa

[0223] ×: Storage modulus is less than 0.7 GPa or more than 3.0 GPa

[0224] (3) Adhesion (die shear strength)

[0225] The obtained RFID inlay was subjected to a chip shear test ("DAGE4000PLUS" manufactured by NORDSON) to peel the chip from the substrate under the conditions of a tool height of 30 μm and a speed of 100 μm / sec, and the chip shear strength at 25°C was evaluated. The adhesion (chip shear strength) was determined based on the following criteria. It should be noted that the conductive paste obtained in Comparative Example 2 was not uniformly mixed, so the chip shear strength could not be measured.

[0226] [Criteria for determining adhesiveness (die shear strength)]

[0227] ○○: Chip shear strength is 7.0N or more

[0228] ○: Die shear strength is 4.0N or more and less than 7.0N

[0229] ×: Chip shear strength is less than 4.0N

[0230] (4) Conductivity reliability

[0231] The obtained RFID inlay was placed in a dark box that blocks external radio waves, and a frequency reader ("Tagformance Pro" manufactured by Voyantic) was used to measure the peak sensitivity at 25°C in the UHF band (860MHz to 920MHz) as the initial peak sensitivity. In addition, the obtained RFID inlay was placed at 85°C and 85% (under a high temperature and high humidity environment) for 72 hours, 168 hours, and 500 hours, and the peak sensitivity at 25°C in the UHF band was similarly measured. Initially, the conduction reliability after being placed under a high temperature and high humidity environment for 72 hours, under a high temperature and high humidity environment for 168 hours, and under a high temperature and high humidity environment for 500 hours was determined according to the following criteria.

[0232] [Criteria for determining initial conduction reliability]

[0233] ○○: Peak sensitivity is lower than -18dBm

[0234] ○: Peak sensitivity is above -18dBm and below -17dBm

[0235] ×: Peak sensitivity is -17dBm or above

[0236] [Criteria for judging conduction reliability after storage in a high temperature and high humidity environment (72 hours, 168 hours, and 500 hours)]

[0237] ○○: The absolute value of the difference from the initial peak sensitivity is less than 2dBm, and the peak sensitivity is less than -17dBm

[0238] ○: The absolute value of the difference from the initial peak sensitivity is 2 dBm or more and less than 3 dBm, and the peak sensitivity is less than -17 dBm

[0239] ×: The absolute value of the difference from the initial peak sensitivity is 3 dBm or more, or the peak sensitivity is -17 dBm or more (a range satisfying at least one of the above conditions)

[0240] The composition of the conductive paste, the structure of the RFID inlay, and the results are shown in Tables 1 to 3 below.

[0241] [Table 1]

[0242]

[0243] [Table 2]

[0244]

[0245] [Table 3]

[0246]

Claims

1. A conductive paste comprising a curable compound, a plurality of conductive particles and a thermal polymerization initiator, The curable compound comprises: a urethane (meth) acrylate having a molecular weight of 1000 or more and an aromatic skeleton, and a polymerizable monomer having a molecular weight of less than 1000 and an aromatic skeleton or an alicyclic skeleton, The viscosity of the conductive paste at 25° C. is 5 Pa·s or more and 50 Pa·s or less.

2. The conductive paste according to claim 1, wherein The content of the conductive particles is 3 parts by weight or more and 30 parts by weight or less relative to 100 parts by weight of the curable compound in the conductive paste.

3. The conductive paste according to claim 1 or 2, wherein The conductive particles have a particle size of 10 μm or less.

4. The conductive paste according to any one of claims 1 to 3, wherein The conductive particles include substrate particles and a conductive portion disposed on a surface of the substrate particles. The conductive portion includes nickel.

5. The conductive paste according to any one of claims 1 to 4, wherein The storage elastic modulus at 25° C. of a cured product obtained by heating the conductive paste at 150° C. for 10 minutes is 0.7 GPa or more and 3.0 GPa or less. 6 . The conductive paste according to claim 1 , which is applied to a substrate having a surface tension of 20 mN / m to 50 mN / m.

7. The conductive paste according to any one of claims 1 to 6, wherein the conductive paste has a bonding surface area of ​​0.50 mm 2 The following chips.

8. The conductive paste according to any one of claims 1 to 7, which is used for obtaining an RFID inlay.

9. An RFID inlay comprising: A substrate having wiring on its surface, Chip, and a bonding portion for bonding the substrate and the chip together; The material of the bonding portion is the conductive paste according to any one of claims 1 to 8, The wiring and the chip are electrically connected via the conductive particles in the adhesive portion.

10. A method for manufacturing an RFID inlay, comprising: A first arrangement step of arranging the conductive paste according to any one of claims 1 to 8 on a surface of a substrate having wiring on the surface; a second placement step of placing a chip on a surface of the conductive paste opposite to the substrate side; and The bonding step is to heat and pressurize the conductive paste to form a bonding portion where the substrate and the chip are bonded together by the conductive paste, and to electrically connect the wiring and the chip through the conductive particles in the bonding portion.

11. The method for manufacturing an RFID inlay according to claim 10, wherein: The substrate is in the shape of a long strip. In the first arrangement step, the second arrangement step, and the bonding step, the RFID inlay is manufactured by conveying the long substrate by a roll-to-roll method.

12. A conductive paste according to any one of claims 1 to 8, wherein the bonding surface area is 0.50 mm 2 The following chips are used.

13. Use of the conductive paste according to any one of claims 1 to 8 for obtaining an RFID inlay.